2020
DOI: 10.1016/j.jechem.2020.02.053
|View full text |Cite
|
Sign up to set email alerts
|

Balancing free and confined metallic Ni for an active and stable catalyst—A case study of CO methanation over Ni/Ni–Al2O3

Abstract: We propose a new strategy to make an active and stable Ni-based catalyst which can be operated in a wide range of reaction temperatures. The ordered mesoporous alumina (OMA) with confined Ni in the pore wall (Ni-OMA) was prepared via the one-pot evaporation induced self-assembly method. By using the incipient impregnation method, different amounts of free Ni were loaded over Ni-OMA (Ni/Ni-OMA) at a fixed total NiO content of 15 wt%. Characterization results confirmed the formation of wellstructured Ni-OMA, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…5a) exhibit a distinct peak at 855.74 eV and a weak satellite one at 861.94 eV, both corresponding to Ni 2+ species 34 . Previous studies have shown that part of Ni 2+ remains on the surface of the sample, which may be due to the strong interaction of smaller Ni NPs with CeO 2 or the formation of a spinel structure between Ni and Al 2 O 3 , which is di cult to reduce at 873 K 35,36 . Furthermore, a new peak observed at 852.52 eV in the reduced catalyst can be attributed to Ni 0 species, still being detectable during the subsequent hydrogenation reaction 37 .…”
Section: Resultsmentioning
confidence: 99%
“…5a) exhibit a distinct peak at 855.74 eV and a weak satellite one at 861.94 eV, both corresponding to Ni 2+ species 34 . Previous studies have shown that part of Ni 2+ remains on the surface of the sample, which may be due to the strong interaction of smaller Ni NPs with CeO 2 or the formation of a spinel structure between Ni and Al 2 O 3 , which is di cult to reduce at 873 K 35,36 . Furthermore, a new peak observed at 852.52 eV in the reduced catalyst can be attributed to Ni 0 species, still being detectable during the subsequent hydrogenation reaction 37 .…”
Section: Resultsmentioning
confidence: 99%
“…As a consequence of their investigation into the Ni/Al2O3 catalyst, Hu, Gao, Ping, Jia, Gunawan, Zhong, Xu, Gu and Su [6] discovered that it was possible to achieve 100% CO conversion over a broad range of reaction temperatures around 300 to 550 °C, and that the CH4 selectivity amplified with growing temperature, peaking at 96.5% at a comparatively low reaction temperature of 350 °C. In the following study, Xiao, Song, Liu, Shi, Ge, Zhu, Liu and Liu [23] investigated the optimal catalyst of NiO/NiO-OMA, the extraordinary activity at temperatures as low as 300 °C was accomplished with the methane space-time yield exceeding 7.6 g gcat -1 h -1 . As a result of the high temperature of 600 °C and 120,000 mL g -1 h -1 of gas hourly space velocity (GHSV), long-standing stability for 400 hours was proven with no evidence of deactivation.…”
Section: Single-supported Ni Catalystmentioning
confidence: 99%
“…Industrially, Co- and primarily Ni-based formulations are the catalysts of choice for the methanation reaction due to their abundance, acceptable activity, and lower cost than Ru, and for that reason also, the most thoroughly studied. , Even though Fe is identified as a high-activity material, it suffers from poor selectivity . One of the challenges with Ni-based catalysts is that they experience fast deactivation via sintering under the high-temperature conditions of the methanation reaction. , Achieving a suitable Ni-support interaction to avoid sintering and developing a low-temperature methanation strategy are active areas of research. , Different supports including Al 2 O 3 , ZrO 2 , CeO 2 , SiO 2 , Y 2 O 3 , metal–organic frameworks have been systematically evaluated, while CeO 2 and ZrO 2 were identified as good supports for the methanation reaction at 613.15 and 573.15 K . A Ni/ZrO 2 -CP catalyst was reported to have 100% CH 4 selectivity at 493.15 K for 100 h in CO methanation, and a bimetallic NiCo/SiO 2 catalyst showed stable operation for 100 h at 653.15 K with superior CO conversion and CH 4 selectivity.…”
Section: Introductionmentioning
confidence: 99%